Effectiveness of Lower Range of High-intensity Statin Therapy in Lowering LDL-C among STEMI Patients - Prajapati, Dipanker; Adhikari, Chandra Mani; Timalsena, Birat Krishna; Maharjan, Nira Shrestha; Dhital, Rolina; Khatri, Anjali; Bogati, Amrit; Manandhar, Reeju; Dhungana, Murari; Safi, Md. Sajjad; Khan, Barkadin; Ghimire, Vijay; et al. (Journal of Nepal Health Research Council, 2024)
Background: Lipid-lowering is an important intervention to reduce cardiovascular morbidity and mortality after ST-Elevation myocardial infarction. This study aimed to assess the proportion of such patients achieving guideline-directed therapeutic low-density lipoprotein cholesterol targets while on lower-range high-intensity statin treatment.Methods: This is a cross-sectional study conducted in Shahid Gangalal National Heart Centre, a tertiary cardiac center in Kathmandu, Nepal, from November 2021 to July 2022 among admitted acute ST-Elevation myocardial infarction patients who were prescribed a lower range of high-intensity statin therapy, Atorvastatin 40mg and Rosuvastatin 20 mg. Clinical characteristics were collected, including lipid parameters at baseline during admission and three months after the treatment. The proportion attaining the guideline-recommended levels was calculated and compared between each statin group. Results: A total of 240 patients were included in this study. The target low-density lipoprotein cholesterol level of less than 1.4mmol/L was noted only in 16.3% and the target reduction by ≥50% from baseline only in 7.1%. Just 3.3 % achieved a target of <1.4 mmol/L and ≥50% reduction from baseline. However, 40.8% of the participants in our study met the 2012 European Society of Cardiology guidelines’ target achievement of less than 1.8 mmol/L. Conclusions: The overall proportion of patients attaining recommended low-density lipoprotein cholesterol levels after recent ST-Elevation myocardial infarction was low when patients were prescribed with a lower range of high-intensity statin, reflecting the need for rigorous follow up including monitoring of lipid levels and intensification of statin dose and type as recommended by international guidelines.Keywords: Low-Density Lipoprotein Cholesterol; secondary prevention; statin; statin intensity; ST-Elevation myocardial infarction.